Safety an efficacy of honey as a supplementary theraphy for chronic obstructive pulmonary disease (COPD) - Muhamad, Rosediani (2017)
Method: A randomized controlled trial involving 34 patients which were allocated to two groups; honey (n=22) and standard care (n=12). Health outcomes were total QOL score using St. George's Respiratory Questionnaire (SGRO) assessed at baseline, two, four and six months. QOL total score changes was analysed using Repeated measure ANOVA. A lower SGRO score indicates better QOL. Results: There were no statistical differences of sociodemographic and QOL between the honey and standard care groups at baseline. The results showed statistically significant baseline and post 2, 4 and 6-months differences of total QOL score in the honey group. Otherwise, only marginally significant difference was detected between baseline and post 2-months in the standard group. Comparison of total QOL score between the two groups based on time favoured the honey group. Honey group demonstrated significantly lower mean total QOL score as compared with the standard group at 4 months (28.89; 95%CI: 21.19, 36.59 vs 42.38; 95%CI: 31.95, 52.81) and 6-months (22.91; 95%CI: 14.94, 30.87 vs 41.95; 95%CI: 31.17, 52.73). Conclusion: Patients with COPD on honey showed better intermediate and long term changes in overall QOL.